Biomarcadores cardíacos em cães com degeneração mixomatosa da valva mitral submetidos a um programa de condicionamento físico - Tristão, Ana Paula Pinto Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
As opposed to human medicine, which already uses the exercise as a therapeutic tool in several heart diseases, it is not common sense for small animal practitioners to recommend such treatment for dogs with heart disease owing to an absence of studies. Cardiac biomarkers may be used to monitor response to treatment and physical activity. Therefore, this study had to goal of assessing how these substances perform in dogs with myxomatous mitral valve disease (MMVD) undergoing a physical exercise program. For this purpose, 15 dogs were ascribed to three groups (in accordance with the leftatrium- to-aorta ratio). Incremental exercise test was performed to detect the lactate threshold. In the following eight weeks, the animals underwent training exercises based on 70% of the lactate threshold velocity. Echocardiographic parameters and cardiac biomarkers (NT-proANP, NT-proBNP, Cardiac troponin I, CK-MB, LDH I and AST) were evaluated at the starting time (M0), and at 4 (M4) and 8 (M8) weeks after the beginning of the exercise protocol. In the LA/Ao <1.4 group, a significant difference was found in NT-proANP at M8 as compared to M0. No differences were documented for the remaining biomarkers throughout the training. Using multivariate analysis, 8 factors were extracted. Factor 1, which comprises fractional shortening and ejection fraction, represented 17.05% of the data variability, while the factors composed by biomarkers showed lower representativeness. Based on these results, it was concluded that the systematic exercise, at least the way it was performed in this investigation, did not promote changes in the concentrations of both the stretch and myocytes injury biomarkers. In addition, multivariate analysis showed that the factors in which biomarkers were included accounted for the lowest part of the total data variability, indicating the low representativeness of these substances in the effects attributed to physical training

Diferentemente da medicina humana que já utiliza o exercício como ferramenta terapêutica em diversas enfermidades cardíacas, na clínica de pequenos animais essa modalidade de tratamento não é indicada para cães cardiopatas devido à falta de estudos nesse campo. A utilização de biomarcadores cardíacos pode ser indicada como meio para monitorizar respostas a tratamentos e atividade física. Assim, o estudo em questão teve como escopo avaliar os biomarcadores cardíacos em cães com doença mixomatosa da valva mitral (DMVM), submetidos ao exercício físico, correlacionando os valores das concentrações de tais substâncias com os índices ecocardiográficos estudados. Para tanto, 15 cães com DMVM foram selecionados e alocados em três grupos, conforme a severidade da enfermidade (baseada no tamanho da relação átrio esquerdo/aorta). O teste de esforço incremental foi realizado para detecção do limiar de lactato e velocidade correspondente. Na sequência, foram realizadas oito semanas consecutivas de treinamento, com base em 70% da velocidade do limiar de lactato. Foram documentas as concentrações sanguíneas dos biomarcadores cardíacos (NT-proANP, NT-proBNP, troponina I cardíaca, CK-MB, LDH I e AST) e as variáveis ecocardiográficas nos momentos inicial (M0), 4 (M4) e 8 (M8) semanas após o início do protocolo de exercício. No grupo AE/Ao<1,4 foi identificada diferença significativa no NT-proANP em M8 comparado ao M0. Para os demais biomarcadores não houve diferença entre grupos e momentos ao longo do condicionamento. Por meio de análise estatística multivariada, foram extraídos 8 fatores, sendo que o fator 1, composto por FEC% e FEJ%, representou 17,05% da variância total dos dados. Já os fatores compostos por biomarcadores apresentaram menor representatividade. Os resultados desta pesquisa permitem concluir que o exercício físico sistematizado, da forma como realizado, não promoveu alteração nas...
Keywords: Cão; Coração - Doenças; Exercícios físicos; Peptídeos; Marcadores bioquímicos; Valvula mitral; Peptides